Diabetes: A review of awareness, comorbidities, and quality of life in India - Bansode, Balasaheb; Nagarajan, Rangasamy (Journal of Social Health and Diabetes, 2017)
Diabetes is one of the major contributors for the noncommunicable diseases. The disease burden due to diabetes is huge, and it not only puts pressure on the diabetes patients but also it adds pressure on the economy of the developing and underdeveloped nations. In India, the burden due to diabetes is more important as every fifth person is a diabetic. This paper reviews awareness and source of knowledge of diabetes, awareness about risk factors, and complications of diabetes in India. The review reveals that (a) awareness about diabetes is less in India; (b) awareness regarding specific risk factors associated with diabetes (obesity, tobacco use, alcohol consumption, and high blood pressure) is found to be less; (c) there is a negative association between duration of diabetes and health-related quality of life; and (d) microvascular complications (retinopathy, nephropathy, neuropathy, and coronary diseases) are major comorbidities affecting the diabetes patients. The review reveals that it is imperative to work effectively toward implementing a holistic program for diabetes prevention by ensuring proper awareness in the community.
Keywords: Awareness; comorbidities; diabetes; India; quality of life